The network structure of ego depletion in Chinese male young adults - Ying, Junji; Ren, Lei; Zhang, Jiaxi; Zhou, Yue; Zhang, Xiaofang; Xiao, Wei; Liu, Xufeng (Frontiers in Psychology, 2023)
Ego depletion refers to the state of low self-control ability as defined by the limited resource model of self-control. The ego depletion aftereffects scale (EDA-S) is a relatively mature tool for evaluating ego depletion. However, the internal structure of EDA-S is not clear. A deeper understanding of its internal structure, especially the core variables, is required to design better interventions to improve people’s ego depletion outcomes and self-control. In the present study, we estimated an unregularized partial correlation network of ego depletion in a sample of 499 male young adults in China, who participated in the EDA-S test, and calculated the centrality index. The results showed that all nodes in the ego depletion network were positively correlated. The five strongest edges were between somatic distress and fatigue, emotional regulation disorder and social withdrawal, work burnout and low self-efficacy, low adherence and low self-efficacy, and fatigue and low processing fluency. Fatigue, low self-efficacy, and emotional regulation disorder had the highest strength centrality, indicating that these three variables may play an important role in the network of ego depletion. This study conceptualizes ego depletion from the perspective of networks in order to provide potential targets for related interventions and insights for future studies.